Bone marrow origin of Ia-positive cells in the medulla rat thymus (The Rockefeller University Press, 1981)
Irradiated rats were reconstituted with bone marrow from F1 hybrids. Ia antigen of donor-bone marrow origin was detected by an immunoperoxidase technique on cryostat sections and found predominantly in the medulla of rat thymus 2 wk after reconstitution. These Ia-bearing cells increased in number with time after reconstitution, but the Ia on the cortical epithelial cells remained of host origin. The nature of the bone marrow-derived cells and their implication for major histocompatibility complex restriction are discussed.